HyWay: Enabling Mingling in the Hybrid World - Vijay, Harsh; Pushp, Saumay; Mittal, Amish; Gupta, Praveen; Gupta, Meghna; Gambhira, Sirish; Chopra, Shivang; Baranwal, Mayank; Arya, Arshia; Manchepalli, Ajay; Padmanabhan, Venkat (Proceedings of the ACM on Interactive, Mobile, Wearable and Ubiquitous Technologies (also ACM UbiComp 2023), 2023)
We present HyWay, short for “Hybrid Hallway”, to enable mingling and informal interactions among physical and virtual users, in casual spaces and settings, such as office water cooler areas, conference hallways, trade show floors, and more. We call out how the hybrid and unstructured (or semi-structured) nature of such settings set these apart from the all-virtual and/or structured settings considered in prior work. Key to the design of HyWay is bridging the awareness gap between physical and virtual users, and providing the virtual users the same agency as physical users. To this end, we have designed HyWay to incorporate reciprocity (users can see and hear others only if they can be seen and heard), porosity (conversations in physical space are porous and not within airtight compartments), and agency (the ability for users to seamlessly move between conversations). We present our implementation of HyWay and the user survey findings from multiple deployments in unstructured settings (e.g., social gatherings), and semi-structured ones (e.g., a poster event). Results from these deployments show that HyWay enables effective mingling between physical and virtual users.